Efficacy of phosphine fumigation for different life stages of Trogoderma inclusum and Dermestes maculatus (Coleoptera: Dermestidae). (March 2020) - Athanassiou, C.G.; Phillips, T.W.; Arthur, F.H.; Aikins, M.J.; Agrafioti, P.; Hartzer, K.L.
Abstract: Despite the importance of dermestid beetles as targets for stored product protection, including the protection of museum artifacts and animal-based products, there are only a few published reports regarding their susceptibility to phosphine fumigation, in contrast with other major stored product insect species. In the current study, we evaluated phosphine against all life stages of Trogoderma inclusum LeConte, the larger cabinet beetle, and Dermestes maculatus (DeGeer), the hide beetle . There were two series of laboratory bioassays; in the first series the concentrations were 0 (control), 50, 100, 200 and 600 ppm, and in the second series the concentrations were 0 (control), 50, 150, 300, 400, 500 and 600 ppm. Both series were carried out on a 5-day insect exposure protocol. The results for both species clearly indicated that eggs were by far the least susceptible life stage, followed by pupae, while most adults and larvae were killed at the 50-ppm concentration. Concentrations between 300 and 400 ppm could be utilized to provide 100% mortality for both species and all life stages. To our knowledge, our results are the first that have provided data regarding efficacy of phosphine for the control of T. inclusum and D. maculatus . Resource managers can utilize our results to more efficiently target these dermestids with specific concentrations of phosphine, depending on the target life stage. Highlights: The efficacy of phosphine was tested against different life stages of Trogoderma inclusum and Dermestes maculatus . For both species, eggs were by far the most tolerant life stage. With the exception of eggs, mortality was 100% or close at 50 ppm of phosphine.